Hormonal Disorders Associated with Polycystic Ovaries Syndrome (PCOS) - Al-Yasiri, Zainab Qasim Muhammad; Sahib, Ahmad Hassan; Al-Musawi, Ali Habeeb Odah (American Journal of Biology and Natural Sciences, 2025)
This study was carried out to look at the hormonal conditions linked to polycystic ovarian syndrome (PCOS) in women living in Thi-Qar Province. 70 samples of women with PCOS who have received a medical diagnosis were included in the research. obtained from outpatient clinics for the period from December 2022 to June 2023, their ages ranged from 20-41 years. Along with 40 samples of healthy women of identical age acting as a control group, the effect of (age, body mass index, marital status, blood group) and its relationship to PCOS was studied. The study showed that the age group most susceptible to PCOS is the second age group (31-41) years, while the percentage decreased in the first age group (20-30) years. According to the results of the current study, a rise in body mass index (BMI) is closely correlated with a higher incidence of polycystic ovaries. The study concluded that there is a relationship between PCOS and blood groups. The highest incidence of the disease was in women of blood group (O), while the percentage decreased to a minimum in women of blood group (AB). Additionally, it was shown that married women were more likely than unmarried women to have PCOS. In comparison to the control group, women with PCOS had significantly higher concentrations of the hormones LH, FSH, Prolactin, Testosterone, and TSH, according to the study's findings (P 0.05). When compared to the control group, the progesterone and estradiol levels in the PCOS patient group were considerably lower (P 0.05).